Quality assurance or quality enhancement: lessons from the UK / Frank Hardman - Hardman, Frank (Pusat Penerbitan Universiti (UPENA), 2005)
This paper reviews current and recent practice in the management of quality assurance in the UK, commenting on strengths and weaknesses. It discusses the impact of quality assessment on policies, structures, distribution of resources and the academic culture of higher education. It also raises questions about the cost effectiveness, reliability and validity of the information provided and whether the evolving systems can accommodate the increasing diversity of higher education. Drawing on the lessons of the UK system, the paper identifies criteria that could be used for informing and evaluating the academic quality assurance system currently being developed by the Malaysian Quality Assurance Division.